Gambaran Tingkat Pengetahuan pada Ojek Online Terhadap Bantuan Hidup Dasar (BHD) - Eko Budi Santoso; Dadi Santoso; Ali Mufti Hisbulloh (Jurnal Ilmiah Kesehatan Keperawatan, 2021)
Background: Online motorcycle taxi drivers are part of a community that is very closely related to traffic. The high number of road accidents requires that anyone who looks to help both lay people or medical personnel. Knowledge of basic life support (BLS) is needed to provide correct help according to health procedures and minimize the risk of death. Objective : Finding out the level of knowledge in online motorcycle taxis on basic life support (BLS). Method : The research method used is the cross sectional approach. Total population of 102 online motorcycle taxi drivers in the Gombong area. The number of samples is 50 respondents. Data collection using a questionnaire. Data analysis using bivariate test is descriptive analysis test with SPSS. Results: The characteristics of the data obtained by the age of online motorcycle taxi drivers in the Gombong area in the final adolescent category were 26 respondents (52.20%). And o Online motorcycle taxi drivers education in the high school / equivalent category was 36 respondents (72.00%). Description of the level of basic life support knowledge in the majority of online motorcycle taxi drivers in the category of less than 31 respondents (62.00%). Descriptions of readiness to help the majority of online motorcycle taxi drivers in a good category of 29 respondents (58.00%). Conclusion: Level of basic life support knowledge (BHD) of readiness to help the online motorcycle taxi driver is lacking. And the results of readiness to help the online motorcycle taxi drivers with good categories.